Right to Work? Assessing India's Employment Guarantee Scheme in Bihar - Dutta, Puja; Murgai, Rinku; Ravallion, Martin; van de Walle, Dominique (Washington, DC: World Bank, 2014)
India’s 2005 National Rural Employment Guarantee Act creates a justiciable 'right to work' by promising up to 100 days of wage employment per year to all rural households whose adult members volunteer to do unskilled manual work. Work is provided in public works projects at the stipulated minimum wage.